A STUDY OF THE ROLLING LOAD CALCULATION MODELS FOR FLAT COLD ROLLING PROCESS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In order to keep the rolling products free of defects, the calculation and constant assessment of the rolling load and torque are required. Many theories for rolling load calculation were developed and among them the most used nowadays still are the Bland and Ford ’s (1948) model and Alexander’s (1971) model in order to achieve a better online control for reversible and tandem cold rolling mills. In this work those models were implemented in a numerical calculation software. The elastic roll’s deformation was taken into account using the Hitchcock´s formula for the deformed roll radius in an iterative way. Those models state that the friction hill (or normal pressure) in the contact arc keeps circular after the elastic deformation. This hypothesis is analysed with a third offline model for calculating the rolling load, named Noncirc (Shigaki et al., 2015), that considers the real roll elastic deformation (not circular anymore). Two cold rolling cases were considered and the friction coefficient was varied in order to evaluate the influence of this parameter on the calculated rolling load/width, the contact arc length and profile and pressure distribution over the contact arc. It was found that both models present imprecise results for both cases analysed, as the thickness is very low and the strip is very work hardened. The noncircular model shows higher loads and larger arc of contacts, but has the drawback of being offline.